A DFT study on Pt doped (4,0) SWCNT: CO adsorption and sensing - Demir, Selin; Fellah, Mehmet Ferdi (Elsevier, 2020)
In this study, Density Functional Theory calculations have been utilized for the platinum doped (4,0) single walled carbon nanotube (SWCNT) in order to investigate the use of the CO gas sensor at room temperature. Hybrid B3LYP method with 6-31G (d,p) basis set for C, O and H atoms and LanL2DZ basis set for N atom have been used in calculations. The structural and electronic properties have been detailed. The charge distributions obtained for structures showed that charge transfer was occurred from the adsorbed CO molecule to carbon nanotube structure as an electron acceptor. The HOMO-LUMO gap of the N doped SWCNT decreased with adsorbing of CO molecule. The results obtained in this study stated that the CO molecule can be adsorbed on N site of SWCNT in order to form the N-C bond with large adsorption energy and significant charge transfer. There is a consistency between the results of previous experimental study and the data of our study. As a conclusion, the electrical conductivity of N doped (4,0) SWCNT cluster increased after a CO molecule adsorption. Accordingly, N doped (4,0) SWCNT have potential for sensing of carbon monoxide at room temperature.
Keywords: (4,0) SWCNT; Pt atom doping; CO; Sensor; Adsorption; DFT